The relationship between tissue differentiation-inducing non-protein coding RNA expression and tumor size in patients with breast cancer: TINCR gene expression in patients with breast cancer - Tan, Shen; Cui, Aimin; Bai, Nan; Zhang, Zicui (Cellular and Molecular Biology, 2023)
Cancer is one of the leading causes of human death worldwide. One of the most common types of malignancy among women is breast cancer, which is the third most common cancer in the world after lung and stomach cancer. This study aimed to evaluate the expression level of Tissue Differentiation-Inducing Non-Protein Coding RNA (TINCR) in adjacent tumor and non-tumor tissues of 60 women with invasive ductal breast cancer. The relationship between TINCR expression and the clinical characteristics of patients has also been studied. For this purpose, total RNA was isolated from breast cancer patients' adjacent tumor and non-tumor tissue. RT Prime Script reagent was then used to convert total RNA to cDNA. The qRT-PCR quantified the TINCR expression level and analyzed the results by paired t-test. In addition, ROC curve analysis was used to evaluate the biomarker power of TINCR in breast cancer tumor tissues. According to the results, a decrease in the level of TINCR was obtained in the tumor tissue of breast cancer patients compared to the adjacent non-tumor tissue (P<0.001). TINCR expression was negatively correlated with tumor size and lymph node metastasis in breast cancer tumor tissue. In general, the decrease in the expression level of TINCR in the tumor tissue of breast cancer patients shows that its expression level can differentiate the adjacent tumor and non-tumor tissue from each other. In addition, TINCR has a lower expression level in breast cancer patients with large tumors, lymph node metastasis, and luminal subgroups A and B.